Power scaling of high-power linearly polarized fiber lasers with <10 GHz linewidth - Chu, Qiuhui; Shu, Qiang; Li, Fengyun; Guo, Chao; Yan, Yuefang; Zhang, Haoyu; Liu, Yu; Tao, Rumao; Lin, Honghuan; Wang, Jianjun (Frontiers in Physics, 2023)
In this work, an all-fiberized polarization maintained fiber lasers has been demonstrated with near top-hat-shaped spectrum laser. By optimizing the modulation signal to generate near top-hat-shaped spectrum, 3kW PM fiber laser has been achieved at <10GHz linewidth with the polarization extinction ratio being 96% and beam quality being 1.156, which is the highest output power with about 10GHz linewidth ever reported, and the further scaling of output power is limited by stimulated Brillouin scattering. By decomposing the mode content, the proportion of fundamental mode in the output laser is above 97%. The stimulated Raman scattering suppression ratio reaches to 72dB at the maximal output power.